Cystatin C Secretion in Blood Derivatives and Cellular Models of Idiopathic Parkinson’s Disease - Kathleen Mommaerts; Anna S. Monzel; Alise Zagare; Sarah L. Nickels; Nico J. Diederich; Laura Longhino; William Mathieson; Paul M. A. Antony; Fay Betsou; Jens C. Schwamborn (Parkinson's Disease)
Parkinson’s disease is an age-related progressive neurodegenerative disorder. A large majority of Parkinson’s disease patients have an unknown etiology, which is classified as idiopathic Parkinson’s disease. Generating disease models directly from idiopathic Parkinson’s disease patients may improve the understanding of the disease pathology. Both neuroprotective and neurodegenerative roles have been suggested for cystatin C in neurodegenerative disease. In Parkinson’s disease, investigations assessing cystatin C levels in different types of biospecimens such as blood, cerebrospinal fluid, and in vitro models have had conflicting results. We present a study assessing cystatin C levels in different biospecimen types originating from the same subjects. Using a sandwich ELISA, we compared cystatin C concentration in blood derivatives (plasma and serum) and culture media of derived models (stem cells, neuroepithelial stem cells, and midbrain organoids) of three idiopathic Parkinson’s disease and three age-matched healthy control subjects with the same CST3 genotype. Genotyping analyses confirmed that all subjects were homozygous AA. The identity of the derived models was confirmed using immunohistochemical staining. Secreted cystatin C concentration was measured in each biospecimen tested. No statistically significant differences in cystatin C concentrations were found between the subjects in any of the biospecimen types. As a personalized marker, a higher cystatin C concentration was shown for some individual patients in the culture medium of midbrain organoids, suggesting a potential involvement in Parkinson’s disease physiopathology. This proof of concept demonstrates that cystatin C is secreted by various idiopathic Parkinson’s disease cell models, including midbrain organoids, which in turn suggests that cystatin C secretion by midbrain organoids might be pertinent in neurodegenerative disease research.